Early Detection and Prognosis of Ovarian Cancer Using Serum YKL-40 - Jakob Dupont; Meena K. Tanwar; Howard T. Thaler; Martin Fleisher; Noah D. Kauff; Martee L. Hensley; Paul Sabbatini; Sibyl Anderson; Carol Aghajanian; Eric C. Holland; David R. Spriggs (2004)
Purpose YKL-40 is a secreted glycoprotein (chitinase family). We compared YKL-40 with two ovarian cancer serum markers, CA125 and CA15-3, for the detection of early-stage ovarian cancer. Materials and Methods Serum YKL-40 levels were assayed by enzyme-linked immunosorbent assay for 46 healthy subjects, 61 high-risk individuals, 33 patients with benign gynecologic processes, and 50 preoperative patients subsequently diagnosed with predominantly early-stage ovarian cancer. Serum CA125 and CA15-3 values were obtained. Results Median YKL-40 level was 28 ng/mL (range, 15 to 166 ng/mL) for healthy subjects, 36 ng/mL (range, 9 to 69 ng/mL) for high-risk individuals without prior cancer, 44.5 ng/mL (range, 5 to 133 ng/mL) for high-risk patients with prior breast cancer, and 38 ng/mL (range, 5 to 67 ng/mL) for individuals with benign gynecologic processes (P = NS). Median preoperative YKL-40 level for ovarian cancer patients was 94 ng/mL (range, 17 to 517 ng/mL; P < .0001 compared with normal and high-risk). YKL-40 was elevated (≥ 62 ng/mL) in 36 (72%) of 50 patients compared with 23 (46%) of 50 and 13 (26%) of 50 patients for CA125 and CA15-3 (P < .008). Twenty (65%) of 31 early-stage patients had elevated serum YKL-40 levels compared with 11 (35%) of 31 and four (13%) of 31 patients for CA125 and CA15-3 (P = .039). YKL-40 levels increased with stage (P < .005), regardless of grade, histology, or patient age. Patients with early-stage tumors with YKL-40 values more than 80 ng/mL had a worse prognosis (71% recurrence v no recurrence [P = .034]). Conclusion YKL-40 may represent a novel marker for the detection of early-stage ovarian cancer. YKL-40 levels in early-stage patients may also predict disease recurrence and survival. The utility of YKL-40 in detection of early-stage ovarian cancer deserves further investigation.